Response of Peatland CO2 and CH4 Fluxes to Experimental Warming and the Carbon Balance - Li, Qian; Gogo, Sébastien; Leroy, Fabien; Guimbaud, Christophe; Laggoun-Défarge, Fatima (Frontiers in Earth Science, 2021)
The function of peatlands as a large carbon (C) reservoir results from the net C uptake under cold, wet and acid environments. However, in the context of global warming, the balance between C input and release is expected to change, which may further alter the C sink of peatlands. To examine the response to climate warming of a temperate Sphagnum peatland which has been invaded by vascular plants, a mesocosm experiment was conducted with open-top chambers (OTCs) to simulate a moderate temperature increase. Gross primary production (GPP), ecosystem respiration (ER) and methane (CH4) emissions were monitored for 2 years. The CO2 and CH4 fluxes were modelled by relating to abiotic and biotic factors, including temperature, water table depth (WTD) and vegetation, in order to calculate the annual C budget. Results showed that the annual cumulated GPP was significantly enhanced by the simulated warming (-602 compared to -501 gC m-2 yr-1 in OTC and control plots, respectively), mainly due to the increase of graminoids biomass by warming. While experimental warming had no significant effect on the annual ER and CH4 emissions (an output of 615 and 500 gC m-2 yr-1 for ER; 21 and 16 gC m-2 yr-1 for CH4 emissions in OTC and control plots, respectively). The annual NEE and C budget were not affected by the short-term experimental warming. The mesocosms under both treatments acted as gaseous C source with 34 and 14 gC m-2 yr-1 output under OTC and control treatment, respectively. This C source was driven by the strong net carbon dioxide (CO2) release during low WTD period in summer, as CH4 emissions only accounted for 0.9-2.2 % of the total C fluxes. Our study identified the effect of moderate warming on the C fluxes, even on a short-term basis. Also our findings highlighted that the response of C fluxes to warming largely depends on the WTD and vegetation composition. Thus long-term monitoring of hydrology and vegetation change under climate warming is essential to examine the their interactions in determining the C fluxes in peatlands.